Mediating Print Culture: Censorship, Revolutionary Journalism and the Manifesto of Equals - Perovic, Sanja (Romanticism and Victorianism on the Net, 2010)
Freedom of expression and censorship are frequently cast in opposing but symmetrical terms. According to the conventional narrative, the right to free speech was acquired when first the American and then the French Revolution overthrew the repressive censorship apparatus of the ancien régime. However this account of increasing emancipation overlooks the important role played by the French Revolution in establishing a new definition of censorship that was both tolerant of free speech and repressive of political difference. This paper contends that precisely when political representation in the widest possible sense is at stake, freedom of speech cannot be reduced solely to a question of rights. It begins by revisiting the Directory period when the enlightened ideal of an unmediated public sphere openly clashed for the first time with the opposing ideal of an ‘unmediated’ or ‘popular’ sovereignty promoted by the radical press. It then focuses on the Conspiracy of Equals to show how the presumed neutrality of the liberal press was forged by repressing competing understandings of the right to free speech. Rather than assume that revolutionary propaganda is the ‘other’ of liberalism, this paper demonstrates the joint origins of both liberal and revolutionary understandings of free speech in the new censorship laws that attempted to separate the message from the medium of revolution.